Pengaruh Medication Therapy Management (MTM) terhadap Outcome Klinik dan Kualitas Hidup Pasien Hipertensi di Puskesmas Kota Yogyakarta - Tiara Dewi Salindri Pratama; Nanang Munif Yasin; Susi Ari Kristina (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Medication therapy management (MTM), is a service model aimed at helping general health problems by preventing morbidity and mortality. Hypertension is a non-communicable disease which is a serious health problem which requires long-term therapy.  This study aims to see the effect of MTM on clinical Outcomes and quality of life of patients in hypertensive patients. This type of research is a quasi experimental one group with a pretest-posttest design. Analysis using paired sample t-test and Wilcoxon test with a significance used P <0,05. Respondents were 70 people, 67,1% were women. The characteristics of the majority age are 55-64 years with a percentage of 51,4%, the majority of education level is high school with 42,8%, non-civil servant jobs with a percentage of 45,7%, the length of diagnosis is dominated by 1-10 years (77,1%) and comorbidities diabetes mellitus occurred the most (10,0%). The results showed that the quality of life increased from before getting MTM 54,4 ± 8,9 and after MTM intervention 60,4 ± 6,6 (P value <0,001). Clinical outcome from systolic 159,2 ± 8,9 mmHg and diastolic 103,8 ± 8,0 mmHg before MTM to 144,1 ± 14,4 mmHg for systolic and 89,7 ± 8,8 mmHg for diastolic with p value <0,001 (p <0,05) for systolic blood pressure and p value: 0,016 (p <0,05) after receiving MTM intervention. Medication Therapy Management (MTM) has a significant influence on improving the quality of life and clinical Outcomes of hypertensive patients. The higher the quality of life of patients, blood pressure becomes more controlled.